Acid dissolution of LiF/(NH4)3AlF6 mixtures obtained in the fluorination of α-spodumene with NH4HF2: Modeling and optimization - Resentera Beiza, Alexander Cristian Jesús; Rosales, Gustavo Daniel; Esquivel, Marcelo Ricardo Oscar; Rodriguez, Mario Humberto (Elsevier, 2023)
Fil: Resentera Beiza, Alexander Cristian Jesús. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina. Universidad Nacional de Cuyo. Facultad de Ciencias Exactas y Naturales; Argentina